2003
DOI: 10.1007/s00467-002-1051-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure following deferoxamine overdose

Abstract: A 17-year-old patient with sickle cell-beta thalassemia undergoing treatment with home iron chelation therapy inadvertently received ten times the recommended dose of intravenous deferoxamine. Acute renal failure (ARF) developed within hours. Immediate treatment with high-efficiency hemodialysis resulted in the prompt return of renal function after only one hemodialysis session. No long-term nephrotoxic effects of the deferoxamine overdose developed after more than 1 year of follow-up. Children with sickle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Papassotiriou et al [ 17 ] detected elevated SCys-C in patients who received DFX at doses of 20-40 mg/kg/day. Acute kidney injury has been reported in 40% of patients on deferoxamine [ 18 ]. None of our patients were taking deferoxamine during this study.…”
Section: Discussionmentioning
confidence: 99%
“…Papassotiriou et al [ 17 ] detected elevated SCys-C in patients who received DFX at doses of 20-40 mg/kg/day. Acute kidney injury has been reported in 40% of patients on deferoxamine [ 18 ]. None of our patients were taking deferoxamine during this study.…”
Section: Discussionmentioning
confidence: 99%
“…Deferoxamine use in high doses is now infrequent and renal dysfunction less common. AKI and acute changes in renal function have been reported in up to 40% of patients given the drug, historically when higher doses and overdoses occurred . In previous randomised studies in thalassaemia, 14% of the cohort given deferoxamine demonstrated increases in serum creatinine.…”
Section: Potential Effects Of Chelation Therapymentioning
confidence: 99%
“…It suggests that those drugs may cause corresponding predicted tissue toxicities. For example, deferoxamine, which targets kidney organ and exhibits great tissue specificity (Z-score = -2.01), has been demonstrated the potential risk of inducing acute renal failure ( Prasannan et al, 2003 ). Moreover, deferoxamine also has significant association with liver tissue (Z-score = -1.97).…”
Section: Resultsmentioning
confidence: 99%